Simulation and validation of injection-compression filling stage of liquid moulding with fast curing resins - Martin, Ffion A.; Warrior, N.A.; Simacek, Pavel; Advani, Suresh; Hughes, Adrian; Darlington, Roger; Senan, Eissa (Springer, 2018)
Very short manufacture cycle times are required if continuous carbon fibre and epoxy composite components are to be economically viable solutions for high volume composite production for the automotive industry. Here, a manufacturing process variant of resin transfer moulding (RTM), targets a reduction of in-mould manufacture time by reducing the time to inject and cure components. The process involves two stages; resin injection followed by compression. A flow simulation methodology using an RTM solver for the process has been developed. This paper compares the simulation prediction to experiments performed using industrial equipment. The issues encountered during the manufacturing are included in the simulation and their sensitivity to the process is explored.